FAKTOR YANG BERHUBUNGAN DENGAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL - Mirawati (Jurnal Ilmiah Citra Kebidanan, 2026)
Background: Hyperemesis gravidarum (HEG), a pregnancy complication characterized by excessive nausea and vomiting, has a global prevalence of 0.3%–3.6% and 1%–3% in Indonesia. In the Bangka Belitung Islands Province, HEG accounts for 2.3% of pregnancies and contributes to maternal morbidity risks. Hospital data from RSUD Kriopanting show an increase from 40 cases (5.63%) in 2022 to 45 cases (5.36%) in 2024. Objective: This study aimed to analyze factors associated with the occurrence of HEG among pregnant women in 2025. Methods: An analytical observational study with a case–control design was applied to 75 respondents, consisting of 25 cases and 50 controls from January to August 2025. Risk factor data were obtained through medical record review and structured interviews. Statistical analysis used the Chi-square test and Odds Ratio (OR) with a 95% confidence level. Results: Significant associations were identified for maternal age (p=0.014; OR=3.45), gestational age (p=0.000; OR=16.00), parity (p=0.005; OR=4.14), nutritional status (p=0.016; OR=3.57), and comorbid history (p=0.004; OR=4.82). Gestational age emerged as the most dominant factor based on the highest OR value. Conclusion: All five factors were significantly associated with HEG, with gestational age identified as the strongest determinant. These findings highlight the need to strengthen risk screening, nutritional education, and promotive–preventive interventions early in pregnancy.